The Impact of Function-Flow Interaction on Left Ventricular Efficiency in Patients with Conduction Abnormalities: A Particle Image Velocimetry and Tissue Doppler Study - Gürel, Emre; Prinz, Christian; Van Casteren, Lieve; Gao, Hang; Willems, Rik; Voigt, Jens-Uwe (Journal of the American Society of Echocardiography, 2016)
The aims of this study were to assess the influence of left bundle branch block (LBBB)–like conduction abnormalities on left ventricular (LV) blood flow patterns and to characterize their potential impact on LV efficiency by measuring the changes in vortex formation and energy dissipation in the left ventricle using echocardiographic particle image velocimetry. Thirty-six subjects were prospectively studied, including 20 patients with pacemakers, six patients with LBBB, and 10 healthy control subjects, all of whom had normal ejection fractions (>50%). In patients with pacemakers, data were acquired in both DDD and AAI modes. Standard grayscale, tissue Doppler myocardial imaging, and contrast-enhanced echocardiographic particle image velocimetric data were acquired, and LV flow patterns were analyzed using dedicated software. Dyssynchrony was quantified by measuring apical transverse motion. Apical transverse motion was significantly higher in patients with LBBB compared with normal control subjects (mean, 4.9 ± 1.9 vs 1.0 ± 0.7 mm; P < .001). Quantitative measures of vortex energy dissipation (relative strength, vortex relative strength, and vortex pulsation correlation) were significantly higher in patients with LBBB (2.05 ± 0.54, 0.53 ± 0.13, and 0.87 ± 0.47, respectively) compared with control subjects (1.48 ± 0.28, 0.33 ± 0.05, and 0.24 ± 0.51, respectively) (P < .02 for all). Vortex duration time in relation to the entire cardiac cycle was shorter in patients with LBBB than in control subjects (28% vs 44%). All findings in both groups were comparable with DDD and AAI. LV flow pattern analysis by echocardiographic particle image velocimetry reveals that conduction delay due to LBBB or pacemaker stimulation in the right ventricle (DDD) disturbs the transfer of kinetic energy during the cardiac cycle and causes less efficient LV function. These data contribute to a better understanding of hemodynamic consequences of conduction delays and may help in the optimization of therapeutic approaches.